Methodological support for the preparation of future teachers for the integrated education of younger students - Zhekibayeva, B.A.; Kalimova, A.D.; Matayev, B.A. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2023)
The article presents one of the results of our work on the scientific project “Scientific-theoretical substantiation and methodological support for ensuring the training of future teachers for the integrated education of younger students”, implemented as part of grant funding for research by young scientists under the Republican project “Zhas Galym for 2022-2024”. The purpose of the article is to substantiate the need for methodological support in the preparation of future teachers for the integrated education of primary school students. The research problem is to find and identify ways and means of preparing future teachers for integrated education in primary school in accordance with the requirements of modern society and the education system as its social substructure. The solution to this problem was reflected in the practical significance of the result presented in the article — the development of an automated training program (ALT) “Scientific and theoretical foundations of integration in learning” and the results of its testing with students of the educational program “Pedagogy and methods of primary education”. The methodological basis of the research is revealed on the basis of a theoretical analysis of the psychological and pedagogical literature on the research problem; legal documents of the Republic of Kazakhstan in the field of education; studying the experience of foreign and Kazakhstani researchers on the preparation of future teachers for the integrated education of younger students. The main results of the study showed that the use of an automated training program has a positive effect not only on the expansion and deepening of knowledge, but also on the development of practical skills, as well as their application in the process of integrated learning in the educational process of primary school.
Бастауыш мектеп оқушыларын біріктіріп оқытуға болашақ мұғалімдерді дайындауды әдістемелік қолдау
Методическое сопровождение подготовки будущих учителей к интегрированному обучению младших школьников
Keywords: integrated education in primary school; training of future primary school teachers; integration of scientific knowledge; methodological support; primary school; automated training program; professional training; methodological materials